Analysis of Cesarean Section Rates According to the Robson Ten-Group Classification System: A Three-Year Retrospective Study - Alaattin Karabulut; Uğurcan Dağlı (Women’s Health and Multidisciplinary Research, 2026)
Background and Aim: This study aimed to analyze cesarean section rates using the Robson Ten-Group Classification System and to identify the main contributing obstetric groups over a three-year period at a tertiary referral center. Materials and Methods: This single-center retrospective cohort study included all eligible deliveries between January 1, 2023, and December 31, 2025. Deliveries were classified according to the Robson system. Group size, group-specific cesarean section rate, and relative contribution to all cesarean deliveries were calculated. Annual changes in overall, primary, and group-specific cesarean section rates were evaluated. Results: Among 6721 deliveries, 4580 were performed by cesarean section, yielding an overall cesarean section rate of 68.1%. The primary cesarean section rate was 33.0%. The overall rate decreased from 70.6% in 2023 to 61.4% in 2025 (p